Lifeways and territorial innovation: values and practices for promoting collective appropriation of territory. (13th November 2017) - Herrera, Obeimar B; Parra, Manuel; Livscovsky, Iris; Ramos, Pedro; Gallardo, Daniela
Abstract: In recent decades, most multilateral organizations and other agents of change have used the theoretical approach of sustainable livelihoods to guide their work. This approach has been criticized in recent years for promoting a short-term materialist focus in development projects, thus limiting its practical usefulness and feasibility. Due to the necessity for renewed proposals, a group of community cargos and researchers have developed a long-term comparative retrospective study that goes beyond the conventional approach. It provides a framework with a broader theoretical scope and applied utility grounded on local self-management: lifeways and territorial innovation. Our constructivist approach, based on Bourdieu´s Social Reproduction theory, is aimed at promoting and triggering a sense of territoriality within the communities and further onto the more extensive territory. Since the work was developed along with people from rural communities, we utilized the concept of Social Learning as to enrich the former theoretical principle.